The 1st International Electronic Conference on Pharmaceutics 2020
DOI: 10.3390/iecp2020-08690
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Efavirenz Complexes Investigated by Solid State and Solubility Studies

Abstract: This short paper investigates the solubilizing ability of various cyclodextrins with efavirenz as well as the formation of solid inclusion complexes of efavirenz with β-CD and γ-CD. (1) Background: Efavirenz is a non-nucleoside reverse transcriptase inhibitor used as first-line treatment for adult and pediatric human immunodeficiency virus type 1 infection (HIV-1). Belonging to class II of Biopharmaceutical Classification System (BCS), efavirenz is poorly water-soluble. Inclusion into cyclodextrins is a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Our results were, therefore, in good agreement with the findings of Sathigari et al [19]. In the batch of efavirenz and γ-CD, a new, low-crystalline phase was formed, indicating the formation of an inclusion complex [20]. The preliminary findings on the formation of γ-CD•EFC prompted further investigation on this host-guest system, which is herein presented.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results were, therefore, in good agreement with the findings of Sathigari et al [19]. In the batch of efavirenz and γ-CD, a new, low-crystalline phase was formed, indicating the formation of an inclusion complex [20]. The preliminary findings on the formation of γ-CD•EFC prompted further investigation on this host-guest system, which is herein presented.…”
Section: Introductionsupporting
confidence: 92%
“…Regarding HPβCD, the literature shows contradictory data, one study depicting it as a good solubiliser, with 60 mM increasing EFV solubility to roughly 1 mM [19], whereas our previous report, in which the isotherm data were collected under the same conditions as those of the present study, revealed it to perform worse than γ-CD, since a concentration of 125 mM of HPβCD was required to solubilise ca. 0.5 mM of EFV [20]. Our study also evaluated HPγCD, which had an isotherm similar to that of HPβCD up to 150 mM and performed slightly worse at higher concentrations [20].…”
Section: Effect Of γ-Cd On Efavirenz Solubilitymentioning
confidence: 71%
See 2 more Smart Citations
“…Due to its structural properties, this molecule appears to be less appropriate for strong interaction with most CDs. The use of βCD nanosuspension [132], γCD [133], HPβCD [133,134] and -γCD [133], or RAMEB [135] could improve its physicochemical (≈10-80-fold solubility enhancements) and pharmacokinetic properties (≈3-fold dissolution rate). Those compositions required a third component to achieve the desired effects.…”
Section: Efavirenzmentioning
confidence: 99%